PERUBAHAN BENTUK PERTUNJUKAN TARI RADAP RAHAYU DI BANJARMASIN KALIMANTAN SELATAN - Edlin Yanuar Nugraheni (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
Changes in the form of dance performance as a means Radap Rahayu Tapung Tawar ceremony in the context of a form of dance entertainment. Changes in shape, can be seen on the element of movement, music, make-up fashion. Radap Rahayu dance forms as a means of Tapung Tawar ceremony amounted to 11 range of motion, the opening song were sung prior to compulsory dance show Radap Rahayu. musik player five people. Position of dancers in front of dancers who Tapung Tawar offered. Music of Radap Rahayu dance as a means of,entertaint the amount depending on the creativity of music players, and adjusted to the demand pattern of the floor. The alteration of fungsion, form and is caused by internal and external factors. The internal factors made by the artist (Banjar tribal socienties), while external factors are changes that are influenced by the Islamic religion, technology, and government (Taman Budaya).Keywords: Dance Radap Rahayu, changes, Banjarmasin.